STRATEGI KAMPANYE PELESTARIAN LINGKUNGAN PADA AKUN INSTAGRAM GERAKAN PEDULI SUNGAI TEMBUNG (@gps.tembung) - Nadia Syafitri (Jurnal Komunikasi, 2024)
Environmental preservation cannot only be carried out by every organization, but environmental conservation should involve all levels of society. Many people no longer care about nature, so many people still throw it into rivers or other areas and people also don't understand the impact of throwing rubbish carelessly. Indonesia is ranked third as the country that produces the most waste in the world. Now the river care movement community is campaigning for environmental preservation by educating the public about the dangers of throwing rubbish into rivers. Through this research entitled "Environmental Conservation Campaign Strategy on the Instagram Account of the Tembung River Care Movement (@gps.tembung)" where this research aims to find out what campaign strategies are carried out by the river care movement community in campaigning for environmental preservation. In this research, researchers used the AIDDA theory. This research is qualitative research with data collection techniques using in-depth interviews, observation and documentation. The results of this research show that the campaign strategy is to determine the audience, manage the message, and choose the media. The communication model used is a persuasive, informative and educational communication model using the Instagram social media account.Batubara District, namely in the Lima Puluh Pesisir sub-district, due to the difficulty in capturing the interest of listeners among teenagers, specifically those under the age of 30.